Redefining synaesthesia? - Cohen Kadosh, R; Terhune, D (2012)
In a thought-provoking paper, Simner (2012) highlights and criticizes a number of assumptions concerning synaesthesia. She specifically takes issue with the following assumptions: (1) synaesthesia is strictly a sensory-perceptual phenomenon; (2) consistency of inducer-concurrent pairs is the gold standard for establishing the authenticity of an individual's synaesthesia; and (3) synaesthesia is not heterogeneous. In the wake of this critique, Simner advances a working definition of synaesthesia as a neurological hyper-association that aims to be more inclusive of its variants. We are very sympathetic to Simner's approach and believe that it raises important points that will advance our understanding of synaesthesia. Here we supplement, and sometimes challenge, some of these ideas.